Communication Strategy of the Nagari Government in Handling Regional Drinking Water Company (PDAM) Conflicts Between Residents in Nagari Panyakalan, Solok Regency - Fatma Ariani; Harisriwijayanti -; Nike Aprianti (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2022)
This study aims to resolve conflicts and overcome complaints from the people of Nagari Panyakalan in the procurement of Regional Drinking Water Companies (PDAMs). This action is carried out through vertical conflict prevention communication strategies, outreach and persuasive communication. Based on research conducted by interviewing Mr. Wali Nagari Panyakalan at the first meeting, the authors explain in Article 15 paragraph 3 the sanctions for destroying or abolishing PDAM drinking water facilities, namely using tools to destroy, revoke and block the operation of the water meter. Reversed position from its original position, installation of a suction pump on the water meter will initially result in a temporary stoppage of the water supply (sealing) and a fine of ten times the maximum annual water consumption